Correlation of Blood Glucose Level, Glycated Hemoglobin, Total Cholesterol and Triacylglycerol Level in Diabetic Patients Attending Tertiary Care Hospital in Eastern Nepal (Global Journal of Science Frontier Research, 2014)
Background: Measurement of blood glucose level and glycated hemoglobin (HbA 1c ) are widely used for long term management of diabetes and its complications. Dyslipidemia, an abnormal level of lipids in blood, is frequently associated with diabetes as a strong risk factor for developing cardiovascular disease, and its control can prevent cardiovascular complications. In this study of diabetic patients, we assessed the blood glucose level, HbA 1c and estimated average glucose (eAG) to determine the correlation with lipid profiles specifically the total cholesterol(TC) and triacylglycerol(TAG).
Keywords: blood glucose; glycated hemoglobin; total cholesterol; triacylglycerol; dyslipidemia; nepal